Prediction of Structure Pouch Magma Volcano Kelud Gravity Data Based Method Using Equivalent Point Mass - Sandy Vikki Ariyanto; Sunaryo Sunaryo; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2014)
The observation has been done by gravity method on the date of 1 July to 12 August 2012 in the Kelud volcano area, Pare, Kediri, Blitar and Ngantang in order to determine the structure of magma pocket. Data analisis from field measurements performed with the following correcting the data includes: convert to mgal, drift correction, tidal correction, latitude correction and topography correction, then obtained a complete Bouguer anomaly values. Subsequently projected onto a flat surface (Damnpey) by using matlab program and resolve regional anomalies with anomaly residual. Qualitative interpretation is done by reading the complete Bouguer anomaly contour pattern, while the quantitative interpretation is done by creating a 2D cross section on the four A-A’, B-B’, C-C’, and D-D’ lines.Based on projection to the flat surface (Dampney) with equivalent field depth of 3500 and equivalent field height of 200 obtained convergent anomaly contour so that anomaly values become stable, based on quantitative interpretation 2D cross section model of A-A’, B-B’, C-C’ and D-D’ lines and describing structure of magma pocket. Slice anomali density contrast of A-A’ at -2,930 gr/cm3 assumed as magma chamber with 900 meter dept while B-B’ slice at -2,910 gr/cm3assumed as magma chamber with 943 meters dept, C-C’ slice at -2,930 gr/cm3 assumed as magma chamber with 914 meters depth, and D-D’ slice at -2,930 gr/cm3 assumed as magma chamber with 943 meters depth.